2014
DOI: 10.1007/s10815-014-0177-4
|View full text |Cite
|
Sign up to set email alerts
|

Calcium- and integrin-binding protein-1 is down-regulated in the sperm of patients with oligoasthenozoospermia

Abstract: Purpose The aim of this study was to determine whether altered expression and distribution of calcium-and integrinbinding protein-1 (CIB1) is involved in the pathogenesis of patients with oligoasthenozoospermia. Methods Sperm samples were obtained from 25 infertile Chinese men who had failed to achieve conception after a period of 1-2 y and had been referred to the Reproductive Laboratory of the second hospital affiliated to the Shandong University of Traditional Chinese Medicine. Participants were divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The testes of CIB1 ‐/‐ male mice exhibited lower mass, histologic irregularities, no detectable spermatids, increased CDC2 /CDK1 expression, and increased cell death compared with testes of CIB1 +/+ male littermates (60). The importance of CIB1 in spermatid health was further substantiated by the work of Sun et al (84), which describes men with oligoasthenozoospermia (low sperm count and motility) who also have lower CIB1 mRNA and protein levels than do men with healthy sperm. The specific role that CIB1 plays in spermatogenesis remains unclear, but is likely linked to its functions in cell proliferation and survival, which has not been deeply explored in meiosis.…”
Section: Cib1 and Diseasementioning
confidence: 95%
“…The testes of CIB1 ‐/‐ male mice exhibited lower mass, histologic irregularities, no detectable spermatids, increased CDC2 /CDK1 expression, and increased cell death compared with testes of CIB1 +/+ male littermates (60). The importance of CIB1 in spermatid health was further substantiated by the work of Sun et al (84), which describes men with oligoasthenozoospermia (low sperm count and motility) who also have lower CIB1 mRNA and protein levels than do men with healthy sperm. The specific role that CIB1 plays in spermatogenesis remains unclear, but is likely linked to its functions in cell proliferation and survival, which has not been deeply explored in meiosis.…”
Section: Cib1 and Diseasementioning
confidence: 95%
“…Sun et al found that the expression level of CIB1 in patients with oligospermia and asthenospermia were lower than those in the control group, while the cyclin-dependent kinase 1 (CDK1) were signi cantly increased, and there was a signi cant correlation between CIB1 mRNA level and CDK1 mRNA level. Therefore, they came to conclusion that CIB1 may be involved in the pathogenesis of oligozoospermia through CDK1 signaling pathway [27]. Yuan et al found that both mRNA and protein expression levels of Cdc2/Cdk1, a regulatory factor of cell cycle, were signi cantly higher in mouse testes with CIB1 deletion than that in the control group, and the proliferation rate of the embryonic broblasts was signi cantly reduced, it is suggested that the expression changes of CDK1 and Cdc2 may destroy the normal interval of Sertoli cell proliferation and lead to the imbalance between the number of Sertoli cells and germ cells, which may lead to the increase of germ cell apoptosis and spermatogenesis defects [21,28].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that male mice deficient in the CIB1 gene were infertile due to impairments in both sperm motility and count (Yuan et al, ). Patients with oligoasthenozoospermia also showed a significant reduction in CIB1 gene expression (Sun et al, ). In a study by Gao et al (), electroacupuncture at CV4, ST36, GV20 and SP6 enhanced germ cell proliferation via improvement of Sertoli cell functions, which may promote the recovery of spermatogenesis and restore normal semen parameters in subfertile males.…”
Section: Discussionmentioning
confidence: 99%